2021
DOI: 10.1002/tea.21733
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a student–teacher–scientist partnership program on high school students' science achievement and attitudes about scientists

Abstract: This article describes the effects of a student-teacherscientist partnership program on high school students' science outcomes. The design was a cluster-randomized trial with an analytic sample of 36 teachers randomly assigned to teach a photosynthesis-and respirationfocused module including student-designed investigations supported by online mentoring from scientists.Forty-nine teachers were randomly assigned to teach photosynthesis and respiration to students as they normally would. The core finding was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…This study not only provides needed rigorous quantitative evidence about the efficacy of the PlantingScience program but also adds to the limited information in the literature about the impact of STSP programs on student outcomes related to both science content knowledge and attitudes about scientists. Before starting the research study, teachers in both groups self-reported their frequency of using common teaching practices, such as small-group discussion, hands-on activities, textbook readings, developing explanations, and so forth in their classrooms (Taylor et al, 2022). These self-reports showed the frequency of these practices was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study not only provides needed rigorous quantitative evidence about the efficacy of the PlantingScience program but also adds to the limited information in the literature about the impact of STSP programs on student outcomes related to both science content knowledge and attitudes about scientists. Before starting the research study, teachers in both groups self-reported their frequency of using common teaching practices, such as small-group discussion, hands-on activities, textbook readings, developing explanations, and so forth in their classrooms (Taylor et al, 2022). These self-reports showed the frequency of these practices was similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Students in both treatment conditions completed pretest and posttest assessments (Taylor et al, 2022). The pretest and posttest forms were identical.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This program centers around a time- and resource-effective hands-on base editing laboratory experiment, with an intended audience of junior and senior high school students who have completed introductory biology coursework. While educating students on base editing technologies was the primary goal, we also aimed to leverage students’ exposure to scientists from diverse backgrounds and invited questions about personal experiences in school, professional development, and the day-to-day life of a graduate student or faculty member within academia (18,19).…”
Section: Introductionmentioning
confidence: 99%